2013
DOI: 10.1186/1471-2407-13-461
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MEG3 inhibits NSCLC cells proliferation and induces apoptosis by affecting p53 expression

Abstract: BackgroundLong non-coding RNAs play an important role in tumorigenesis, hence, identification of cancer-associated lncRNAs and investigation of their biological functions and molecular mechanisms are important for understanding the development and progression of cancer. Recently, the downregulation of lncRNA MEG3 has been observed in various human cancers. However, its role in non-small cell lung cancer (NSCLC) is unknown. The aim of this study was to examine the expression pattern of MEG3 in NSCLC and to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
311
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(330 citation statements)
references
References 36 publications
17
311
2
Order By: Relevance
“…Furthermore, lncRNAs have been identified to play a major role in the development and progression of different cancers. Some well-defined lncRNAs, including HOTAIR (Gupta et al, 2010;Kim et al, 2013;Nakagawa et al, 2013), MEG3 (Lu et al, 2013) and LOC285194 (Qi et al, 2013) have been reported to be strongly associated to survival of cancer patients, thus they have been determined as prognostic indicators for a delete certain types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lncRNAs have been identified to play a major role in the development and progression of different cancers. Some well-defined lncRNAs, including HOTAIR (Gupta et al, 2010;Kim et al, 2013;Nakagawa et al, 2013), MEG3 (Lu et al, 2013) and LOC285194 (Qi et al, 2013) have been reported to be strongly associated to survival of cancer patients, thus they have been determined as prognostic indicators for a delete certain types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MEG3 has already been found to promote cellular proliferation and induce apoptosis in non-small cell lung carcinoma (NSCLC) by affecting TP53 target gene expression. 40 This suggests that the oncogene regulates a lncRNA, MEG3, and that the lncRNA can regulate many downstream targets. Taken together, the association of lncRNA expression with mutational status potentially implicates some of the onco-lncRNAs in specific well-known cancer pathways.…”
mentioning
confidence: 99%
“…To date, lncRNAs, including maternally expressed 3 (MEG3) and papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3), have been reported to function as tumor suppressors. Downregulation of MEG3 has been observed in various types of human cancer, and the lncRNA has been demonstrated to inhibit cancer cell proliferation and induce apoptosis (27,28). PTCSC3 is a newly identified, thyroid-specific lncRNA that is significantly downregulated in thyroid cancer.…”
mentioning
confidence: 99%